Effect of fluoride gels supplemented with sodium trimetaphosphate on enamel erosion and abrasion: In vitro study - Pancote, L. P. [UNESP]; Manarelli, M. M. [UNESP]; Danelon, M. [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP] (Elsevier B.V., 2014)
Objective: This in vitro study aims to evaluate the effect of low fluoride (F) gel associate sodium trimetaphosphate (TMP) on erosion with or without abrasion.Design: Enamel blocks (4 mm x 4 mm) selected through surface hardness (SH) is divided into five groups (n = 12): gel without F and TMP (placebo), gel containing 4500 ppm F (4500), gel containing 4500 ppm F plus TMP5% (4500 TMP5%), gel containing 9000 ppm F (9000), and gel containing 12,300 ppm F (acid gel). Those groups were additionally subdivided into conditions of erosion (Ero) and of erosion plus abrasion (Ero/Abra). The blocks have undergone a single application of gel on the first day of the study. The erosion challenge was produced by Sprite Zero(R) for five minutes four times a day and abrasion was carried out by machine brushing for 15 s. After the challenges, the surface hardness (%SH), wear and cross-sectional hardness (Delta KHN) were analyzed. The data were analyzed using a 2-way ANOVA test followed by a Student-Newman-Keuls (p < 0.05).Results: Lower values of %SH, wear and Delta KHN were observed for erosion challenge (p < 0.001). The %SH was lower in groups treated with fluoride gels, differing in the placebo (p < 0.05). With addition of TMP to the gel 4500, enamel wear was lower when compared with another groups (p < 0.05).Conclusion: In vitro conditions, the 4500 5%TMP gel showed greatest effect against erosion and erosion/abrasion. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Fluoride gels; Tooth erosion; Tooth abrasion; Topical fluorides; Dental enamel; Polyphosphates